Performance Evaluation Judgments: Effects of Prior Experience Under Different Performance Evaluation Schemes and Feedback Frequencies - Frederickson, James R.; Peffer, Sean A.; Pratt, Jamie (Journal of Accounting Research, 1999)
James R. Frederickson, Sean A. Peffer, Jamie Pratt, Performance Evaluation Judgments: Effects of Prior Experience Under Different Performance Evaluation Schemes and Feedback Frequencies, Journal of Accounting Research, Vol. 37, No. 1 (Spring, 1999), pp. 151-165